2020
DOI: 10.1101/2020.02.13.947275
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gene expression noise can promote the fixation of beneficial mutations in fluctuating environments

Abstract: Nongenetic phenotypic variation can either speed up or slow down adaptive evolution. We show that it can speed up evolution in environments in which available carbon and energy sources change over time. To this end, we use an experimentally validated model of Escherichia coli growth on two alternative carbon sources, glucose and acetate. On the superior carbon source (glucose), all cells achieve high growth rates, while on the inferior carbon source (acetate) only a small fraction of the population manages to … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 83 publications
1
6
0
Order By: Relevance
“…2009), as suggested by recent experimental studies (B贸di et al. 2017; Schmutzer and Wagner 2020). However, this claim is in contradiction with classical theory that states that phenotypic noise always reduces the selection gradient (Lande 1975; Gavrilets and Hastings 1994; Wang and Zhang 2011; Mineta et al.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…2009), as suggested by recent experimental studies (B贸di et al. 2017; Schmutzer and Wagner 2020). However, this claim is in contradiction with classical theory that states that phenotypic noise always reduces the selection gradient (Lande 1975; Gavrilets and Hastings 1994; Wang and Zhang 2011; Mineta et al.…”
supporting
confidence: 52%
“…Because phenotypic noise increases the genotypic fitness of an organism far from the fitness optimum, it seems logical that it should facilitate adaptive evolution of the mean phenotype by increasing the fitness of beneficial mutations (Zhang et al 2009), as suggested by recent experimental studies (B贸di et al 2017;Schmutzer and Wagner 2020). However, this claim is in contradiction with classical theory that states that phenotypic noise always reduces the selection gradient (Lande 1975;Gavrilets and Hastings 1994;Wang and Zhang 2011;Mineta et al 2015;Tufto 2015).…”
mentioning
confidence: 96%
“…Second, somatic genotypic exploration allows selection to act on the potential of genotypes to produce non-heritable adaptive phenotypes, eventually rendering those phenotypes heritable. This makes somatic genotypic exploration akin to the genetic assimilation of plastic phenotypes triggered by environmental conditions [89][90][91][92] or by the stochasticity or "noise" of cellular processes [54,[93][94][95]. Within this context, the so-called "look-ahead effect" [54] is particularly relevant; in this model, phenotypic mutations caused by transcription or translation errors create potentially adaptive protein variants, offering a mechanism for channeling populations towards adaptive genotypes, as in our model.…”
Section: Evolutionary Implications Of Somatic Genotypic Explorationmentioning
confidence: 99%
“…As a result, we hypothesize that the plasticity of demographic noise holds more generally in selforganized systems (52), including colonies, biofilms, spatially-structured microbiomes, and solid cancer tumors, which would be interesting avenues for future study. Additionally, other phenotypic traits have been predicted to influence colony patterning and demographic noise and it would be interesting to test their influence on demographic noise in future work, including that of cell-cell and cell-substrate adhesion (53)(54)(55), cell orientations (32), cell elasticity (32), and variation in single cell growth rates (56,57) and lag times (58,59).…”
Section: Supplementary Section 25)mentioning
confidence: 99%